Perceptions of Patient Portal Use for Advance Directive Documentation among Older Adults with Multiple Chronic Conditions. Issue 3 (2nd July 2020) - Portz, Jennifer Dickman; Lum, Hillary D.; Bull, Sheana; Boxer, Rebecca S.; Bekelman, David B.; Ford, Kelsey L.; Gleason, Kathy; Casillas, Alejandra; Bayliss, Elizabeth A.
Abstract: Patient portals can play an innovative role in facilitating advanced care planning (ACP) and documenting advance directives (ADs) among older adults with multiple chronic conditions. The objective of this qualitative sub-study was to (1) understand older adults' use of an ACP patient portal section and (2) obtain user-design input on AD documentation features. Although some older adults may be reluctant, participants reported likely to use a portal for ADs with proper portal design and support.